SISTEM INFORMASI PENGOLAHAN DATA PERPUSTAKAAN BERBASIS DESKTOP PADA YAYASAN PENDIDIKAN TANIMBAR LESTARI - Gustina, Dian; Sumbaryadi, Achmad; Nurbaeti, Riski (Fakultas Teknik Universitas Persada Indonesia YAI, 2018)
Tanimbar Lestari Education Foundation is one of the schools from elementary to senior high school inJakarta. In 1994, it was determined to improve the infrastructure and performance of teachers in order to becomean international school. However, infrastructure improvements are not accompanied by the development ofinformation systems within this school. One of them is not yet computerized library management system, withthe implementation of manual system make less maximal performance library. Some examples, time-consumingbook-keeping systems and book-keeping loans are still recorded in book-keeping. This makes the service to thestudents become less good. By analyzing the symptoms of the problem, we can draw conclusions about anopportunity to develop a library application that is applied to this school. The application is in the form ofDesktop which contains library activities that were previously done manually into a computerized system, suchas managing a list of books owned by the library in the form of a database. This application is built with userinterface display that is user friendly, so for the user that the library employee can use it easily. Views createdusing Netbeans 7.0 IDE, Database using MySql.